The pyroptosis-related gene signature predicts prognosis and reveals immune microenvironment infiltration in reclassified glioblastoma based on 2021 WHO classification - Zheng, Xiaohong; Pan, Zhangchi; Chen, Lina; Wang, Can; Li, Wenbin (Frontiers in Immunology, 2025)
BackgroundGlioblastoma (GBM) is a highly malignant brain tumor with a poor prognosis. The WHO Classification of Tumors of the Central Nervous System (WHO CNS5) reclassified GBM in 2021. Pyroptosis, as an inflammatory form of programmed cell death, could regulate tumor cell proliferation, invasion, and metastasis. However, the role of pyroptosis in the newly defined GBM and its correlation with immunity have not yet been elucidated.MethodAccording to the 2021 WHO CNS5, a total of 209 newly defined GBM samples from The Cancer Genome Atlas (TCGA) cohort were included for analysis. The Chinese Glioma Genome Atlas (CGGA) cohort was used as the validation set. The prognosis model was built by Least Absolute Shrinkage and Selection Operator (LASSO) Cox analysis. The nomogram was conducted to confirm the prognostic value of risk score. ESTIMATE, CIBERSORTx, and ImmuCellAI were used to investigate immune infiltration. Quantitative real-time polymerase chain reaction (RT-qPCR) and immunohistochemistry were performed to validate PLCG1 and NOD2 genes in the prognostic model.ResultsThe risk score model including the two genes was built. The experimental results verified that elevated NOD2 expression and reduced PLCG1 expression in GBM represent poor prognosis with a higher risk. This risk score model could predict the survival rates of patients with GBM with medium to high accuracy. The benefit of chemotherapy or radiotherapy was greater in the high-risk group than in the low-risk group. Moreover, the high-risk group had stronger immune activity and poorer immunotherapy response.ConclusionsIn summary, our study provided strong evidence for the prognosis and clinical management of the newly defined GBM from bioinformatics and experimental analysis. Furthermore, our findings provided a foundation for future research targeting pyroptosis and its immune microenvironment to improve GBM prognosis.